An Overview of Biopolymeric Electrospun Nanofibers Based on Polysaccharides for Wound Healing Management - Andreea-Teodora Iacob; Maria Drăgan; Oana-Maria Ionescu; Lenuța Profire; Anton Ficai; Ecaterina Andronescu; Luminița Georgeta Confederat; Dan Lupașcu (MDPI AG, 2020)
Currently, despite the thoroughgoing scientific research carried out in the area of wound healing management, the treatment of skin injuries, regardless of etiology remains a big provocation for health care professionals. An optimal wound dressing should be nontoxic, non-adherent, non-allergenic, should also maintain a humid medium at the wound interfacing, and be easily removed without trauma. For the development of functional and bioactive dressings, they must meet different conditions such as: The ability to remove excess exudates, to allow gaseous interchange, to behave as a barrier to microbes and to external physical or chemical aggressions, and at the same time to have the capacity of promoting the process of healing by stimulating other intricate processes such as differentiation, cell adhesion, and proliferation. Over the past several years, various types of wound dressings including hydrogels, hydrocolloids, films, foams, sponges, and micro/nanofibers have been formulated, and among them, the electrospun nanofibrous mats received an increased interest from researchers due to the numerous advantages and their intrinsic properties. The drug-embedded nanofibers are the potential candidates for wound dressing application by virtue of: Superior surface area-to volume ratio, enormous porosity (can allow oxy-permeability) or reticular nano-porosity (can inhibit the microorganisms'adhesion), structural similitude to the skin extracellular matrix, and progressive electrospinning methodology, which promotes a prolonged drug release. The reason that we chose to review the formulation of electrospun nanofibers based on polysaccharides as dressings useful in wound healing was based on the ever-growing research in this field, research that highlighted many advantages of the nanofibrillary network, but also a marked versatility in terms of numerous active substances that can be incorporated for rapid and infection-free tissue regeneration. In this review, we have extensively discussed the recent advancements performed on electrospun nanofibers (eNFs) formulation methodology as wound dressings, and we focused as well on the entrapment of different active biomolecules that have been incorporated on polysaccharides-based nanofibers, highlighting those bioagents capable of improving the healing process. In addition, in vivo tests performed to support their increased efficacy were also listed, and the advantages of the polysaccharide nanofiber-based wound dressings compared to the traditional ones were emphasized.